المستخدم في تخدير أنواع من اسماك الكارب Eugenia caryophyllata,clove بعض مواصفات القرنفل - ألعبيدي, حازم جواد; ألعبيدي, حازم جواد; ألبياتي, نمير محمود; دحام, حداوي محمد; صبري, سوزان وحيد; الجشعمي, خلود جميل (Al-Nahrain Journal of Science, 2013)
Abstract:Three experiments were conducted to study some properties of Clove, Eugenia caryophyllata as an anesthetic for three species of carp fish. The First experiment studied the effect of clove on Grass carp, Ctenopharyngodon idella and Silver carp, Hypophthalmychthys molitrix. The average time for light sedation was 165 sec. for both, and deep sedation time was 465 and 330 sec. respectively, while the recovery times were 150 and 180 sec. respectively. In the second experiment, clove effect was compared with MS-222 anesthetic which is used widely in fishery activities. No significant difference was found between them in light sedation, but it was significant (P≤0.05) in deep sedation and recovery times. The third experiment was conducted to study the ability of clove solution on keeping its effects carp through storage. Result showed that clove solution in concentration of 190 mg/L may maintain its effect on fish for five days from preparation.